What Has Place Got to Do With It? Hot Spots Policing to Address Physical and Mental Health - Jensen, Rachel H. (Journal of contemporary criminal justice, 2019)
In the last few decades of criminological research, the contextual concept of place has become a widely discussed and studied topic. Currently, one of the most studied and discussed place-based strategies is hot spots policing, the study of crime patterns at micro-geographic places. Since the 1980s, hot spots policing has become an important and empirically validated law enforcement intervention. One of the most novel questions about hot spots policing is whether it can be used to address other issues such as the intersection of crime, place, and health. Do concentrated patterns of physical and mental health issues mirror the patterns of crime at places? If so, can hot spots policing guide police interventions? This article reviews the current state of public health and place-based crime patterns to synthesize the concept of place-based interventions for health and crime. The article concludes with implications for the scholars and practitioners.